2021
DOI: 10.1021/acsearthspacechem.0c00296
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Dependent Viscosity of Secondary Organic Aerosol from Ozonolysis of β-Caryophyllene: Measurements, Predictions, and Implications

Abstract: To predict important secondary organic aerosol (SOA) properties, information on viscosity or diffusion rates within SOA is needed. Ozonolysis of β-caryophyllene is an important SOA source; however, very few viscosity or diffusion rate measurements have been performed for this SOA type and none as a function of relative humidity (RH). In this study, we measured viscosity as a function of RH for SOA generated from the ozonolysis of β-caryophyllene using the poke-flow technique. At an RH of 0 and 48%, the viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
69
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 125 publications
5
69
1
Order By: Relevance
“…Different types of SOAs generated in environmental chambers and flow reactors have been examined. The dynamic viscosities of some types of SOA particles (e.g., generated from toluene and diesel vapors) ranged from 10 −3 to 10 8 Pa s, which is approximately equal to the range of viscosities between that of water and tar pitch, depending on the RH, oxidation state, and chemical composition (Mikhailov et al, 2009;Virtanen et al, 2010;Vaden et al, 2011;Koop et al, 2011;Saukko et al, 2012;Renbaum-Wolff et al, 2013a;Hao et al, 2014;Kidd et al, 2014;Bateman et al, 2015;Athanasiadis et al, 2016;Grayson et al, 2016Grayson et al, , 2017Hinks et al, 2016;Hosny et al, 2016;Rothfuss and Petters, 2017;Yli-Juuti et al, 2017;Petters et al, 2019;Gervasi et al, 2020). In addition to the viscosity of SOA, the viscosity effects of inorganic salts should also be investigated to better understand the viscosities and phase states of atmospherically relevant mixed particles.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Different types of SOAs generated in environmental chambers and flow reactors have been examined. The dynamic viscosities of some types of SOA particles (e.g., generated from toluene and diesel vapors) ranged from 10 −3 to 10 8 Pa s, which is approximately equal to the range of viscosities between that of water and tar pitch, depending on the RH, oxidation state, and chemical composition (Mikhailov et al, 2009;Virtanen et al, 2010;Vaden et al, 2011;Koop et al, 2011;Saukko et al, 2012;Renbaum-Wolff et al, 2013a;Hao et al, 2014;Kidd et al, 2014;Bateman et al, 2015;Athanasiadis et al, 2016;Grayson et al, 2016Grayson et al, , 2017Hinks et al, 2016;Hosny et al, 2016;Rothfuss and Petters, 2017;Yli-Juuti et al, 2017;Petters et al, 2019;Gervasi et al, 2020). In addition to the viscosity of SOA, the viscosity effects of inorganic salts should also be investigated to better understand the viscosities and phase states of atmospherically relevant mixed particles.…”
Section: Introductionmentioning
confidence: 96%
“…Most studies on this topic have focused on the determination of the viscosities and phase state of secondary organic aerosols (SOAs) (Mikhailov et al, 2009;Virtanen et al, 2010;Koop et al, 2011;Vaden et al, 2011;Saukko et al, 2012;Renbaum-Wolff et al, 2013;Hao et al, 2014;Kidd et al, 2014;Bateman et al, 2015;Athanasiadis et al, 2016;Grayson et al, 2016;Hinks et al, 2016;Hosny et al, 2016;Yli-Juuti et al, 2017;Petters et al, 2019;Wallace and Preston, 2019;Gervasi et al, 2020;Schmedding et al, 2020). Different types of SOAs generated in environmental chambers and flow reactors have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Grayson et al (2016) used the poke-and-flow technique to measure the viscosity of α-pinene derived SOA at CSOA between 120 and 14,000 μg m -3 . Maclean et al (2021) recently completed a similar poke-and-flow study with β-caryophyllene derived SOA. Kidd et al (2014) found similar results by studying SOA impaction patterns onto a germanium crystal, which also permitted FTIR spectroscopic analysis of chemical composition.…”
mentioning
confidence: 99%
“…Environmental factors, such as relative humidity and temperature, can influence the viscosity of the particle [4,5]. The effect of relative humidity on viscosity has been the focus of extensive studies over the past few decades [6][7][8][9][10]. In higher relative humidity conditions, the higher water content in the particle phase decreases the viscosity of the particle.…”
Section: Introductionmentioning
confidence: 99%